Análise dinâmica de pisos mistos em aço-concreto submetidos a atividades humanas rítmicas - Loose, Juliane Klug (2007)
The application of dynamic analysis in structures is growing together with the new technologies of construction. Knowledge about the behavior of materials and its consequent optimized usage allow making structures more and more slender. This tendency of design are leading to structures systems with natural frequencies much and much lower and, therefore closer to the frequency of the dynamic excitation associated to the human beings activities, such as: walking, running and jumping. As a consequence, dynamic loads due to human rhythmic activities can be enough to cause frequencies near the resonance, making the system sufficiently vulnerable to the effects of vibrations, exceeding the recommended limits for human comfort, resulting in discomfort for people. This work intends to study the behavior of composite floor systems (steel-concrete), subjected to human rhythmic activities like aerobic activities and free jumps. For such, analysis in composite floor models will be done using the Finite Element Method (FEM). It was considered the usual techniques of discretization using the computer program Ansys. The beams are simulated by finite elements considering flexion and torsion effects. The concrete floors are simulated by elements with membrane capability. The dynamics loads were modeling using diferents metodologies. One of these, uses experimental parameters that considere effects produced by crowds, and other, use parameters from international recomendations. Later, the results obtained, in terms of the maximums accelerations (peaks accelerations), are confronted and compared to those supplied by the technical literature available about the subject, from the point of view of human comfort. The results obtained in this study show that composite floors analyzed are submitted to high accelerations that can be cause problems, because exceed the limits associated to the human comfort.